Development of concentric semi-automated manipulator for assembly process - Tan, Kai Jin (2018)
This thesis is about the design, modelling and comparison studies on the concentric loading design used in a pneumatic manipulator. Pneumatic manipulator is one of the material handling system widely used in industries. Applications of pneumatic manipulator enable flexible facilities reconfiguration and tool sharing among various products. Existing design requires many components due to the mechanism design concept, which makes the size of the mechanism bulky and heavy. Several designs of powered assisted manipulator were studied. The working principle of the pneumatic manipulator complies with the equilibrium of the moment. Force to balance the lifted weight must be maintained constantly. Piston rod of the cylinder to apply force must be guided precisely in vertical and the relevant parts of the guide connected must be flexible. Concentric loading was designed with different mechanism concept required less components and fabrication parts but enabled the force from the cylinder to balance the working load and was applied vertically and constantly on a specified spot. Two nos. of ball rollers replaced 8 nos. of existing ball bearing side roller mechanism to reduce the cost and maintain the same functionalities. The integration of different parts into one part was studied and applied. Side plates were used as the guide for the side roller mechanism and as a support to the mechanism body. Reduction of purchasing components and fabrication parts aim to reduce the maintenance cost and components inventory cost in a long run. Since some of the concepts of the mechanism were changed, some ball bearing rollers and fabrication parts to cover existing mechanism were not further required. An actual model of a pneumatic manipulator in industry which has a combination of a few manipulator design characteristics and available in the market was used as a case study. Comparison studies between this selected model of the pneumatic manipulator and a concentric loading design pneumatic manipulator were carried out. Simulation on the concentric loading mechanism was done to avoid potential problem before the prototype was built. Overall, the results showed a 28% reduction in weight of the manipulator mechanism body, 8.9% to 32% reduction of size in width, length and height of the manipulator mechanism body and a 39% reduction in cost of the manipulator mechanism body. Fabrication parts of manipulator mechanism body were reduced from 48 pieces to 20 pieces. A prototype was built to test on the functionality of the concentric loading mechanism. Detail drawings of the prototype were then created and send for fabrication. Standard components were purchased. A pneumatic controlled circuit was developed to operate the prototype. Several observations on the concentric loading mechanism were done during the prototype mechanism testing. The working condition of the concentric loading mechanism was recorded and discussed. It showed that the mechanism of the prototype working well and proved that concentric loading mechanism meet the requirement of moment concept and able to lift and balance the lifted load. The transition of the balancing mechanism was smooth. Other observations were discussed for future studies.